2015
DOI: 10.1080/03630242.2015.1022686
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Adolescence and Abdominal Obesity in Adulthood: A Case-Control Study Among Women Shift Workers

Abstract: Physical activity may have a protective effect against abdominal obesity, an important risk factor for cardiometabolic diseases. Thus, the aim of this study was to examine the association between the practice of physical activities in adolescence and abdominal obesity in adulthood among women shift workers in Southern Brazil in 2011. This case-control study included 215 cases (waist circumference greater than or equal to 88 cm) and 326 controls. For both the case and control groups, participation in leisure-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
2
5
0
1
Order By: Relevance
“…Although the number of sport disciplines participated in correlated with the volume of physical activity (Table 1), the result between waist circumference and number of sport disciplines persisted after adjusting for overall volume of physical activity. In accordance with our findings, Garcez et al 33 showed that women who had participated in five or more different physical activities in adolescence were less likely to be abdominal obese in adulthood. The benefits of enhancing diverse sport participation may be manifold.…”
Section: Diverse Sport Participationsupporting
confidence: 93%
“…Although the number of sport disciplines participated in correlated with the volume of physical activity (Table 1), the result between waist circumference and number of sport disciplines persisted after adjusting for overall volume of physical activity. In accordance with our findings, Garcez et al 33 showed that women who had participated in five or more different physical activities in adolescence were less likely to be abdominal obese in adulthood. The benefits of enhancing diverse sport participation may be manifold.…”
Section: Diverse Sport Participationsupporting
confidence: 93%
“…In Southern Brazil, a case-control study investigated the association between the practice of physical activities in adolescence and AO in adulthood among women who were shift workers. Women who participated in five or more physical activities in adolescence were 50% less likely to have AO than women who participated in one activity or no physical activities (OR = 0.50 95% CI: 0.27;0.93) [106].…”
Section: Physical Activitymentioning
confidence: 98%
“…At the same time, unhealthy behavior was also observed in subjects who smoked. Some researchers have pointed to the existence of dangerous behaviors that included smoking, lower physical activity, and unhealthy eating habits in adults, and these behaviors were usual among low SES subjects [106,118].…”
Section: Smokingmentioning
confidence: 99%
“…Several studies analysed the relationship between different aspects of a healthy diet ( 25 27 , 49 , 65 67 ) , physical fitness ( 28 , 29 , 34 ) , sleep duration ( 35 , 36 ) or body composition ( 37 , 38 , 68 ) in adolescence and CVD risk markers in later life. There is robust evidence that a healthy diet in adolescence is related to cardiovascular health later in life ( 25 27 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies investigated the effect of physical activity on cardiometabolic risk. Inverse associations between a predominantly active lifestyle and body composition ( 28 , 29 ) , and triglycerides have been found ( 30 , 31 ) . The results regarding sedentary behaviour (i.e.…”
Section: Introductionmentioning
confidence: 99%